Twisters [videorecording (Blu-Ray)] - Smith, Mark L.; Kosinski, Joseph, 1974-; Mindel, Daniel; Wallfisch, Benjamin; Edgar-Jones, Daisy, 1998-; Powell, Glen, 1988-; Ramos, Anthony; Perea, Brandon, 1995-; Tierney, Maura, 1965-; Lane, Sasha, 1995- (Universal, 2024)
A pair of storm chasers risk their lives in an attempt to test an experimental weather alert system.